When in doubt follow your nose—a wayfinding strategy - Meilinger, Tobias; Frankenstein, Julia; Bülthoff, Heinrich H. (Frontiers in Psychology, 2014)
Route selection is governed by various strategies which often allow minimizing the required memory capacity. Previous research showed that navigators primarily remember information at route decision points and at route turns, rather than at intersections which required straight walking. However, when actually navigating the route or indicating directional decisions, navigators make fewer errors when they are required to walk straight. This tradeoff between location memory and route decisions accuracy was interpreted as a “when in doubt follow your nose” strategy which allows navigators to only memorize turns and walk straight by default, thus considerably reducing the number of intersections to memorize. These findings were based on newly learned routes. In the present study we show that such an asymmetry in route memory also prevails for planning routes within highly familiar environments. Participants planned route sequences between locations in their city of residency by pressing arrow keys on a keyboard. They tended to ignore straight walking intersections, but they ignored turns much less so. However, for reported intersections participants were quicker at indicating straight walking than turning. Together with results described in the literature, these findings suggest that a “when in doubt follow your nose strategy” is applied also within highly familiar spaces and might originate from limited working memory capacity during planning a route.